P002 Using anthropometric measurements to determine the ideal mattress firmness. (19th November 2019) - Shore, Hannah; Richards, Jim; Chohan, Ambreen
Abstract : Introduction: There is limited evidence to suggest that a 'one-size fits all' mattress provides the appropriate support in individuals with diverse body shapes, a greater understanding of how different mattresses affect the human body is required. By having a more objective approach to choosing a mattress, individuals may improve quality of sleep. Materials: A ten-camera infrared movement analysis system recorded Upper-Mid Thoracic, Mid-Lower Thoracic, Lower Thoracic–Upper Lumbar, Upper-Lower Lumbar and Lower Lumbar–Pelvic areas of the spine in side lying. Deviations away from a neutral position were assessed under different conditions. Three aesthetically identical mattresses were tested, internally each mattress contained a different firmness of spring unit (soft, medium, firm). In addition, height, weight, shoulder width and hip circumference measurements were taken to determine differences in body types. Results: Spinal alignment was assessed on sixty healthy participants and no significant differences were seen between the different mattress configurations. However further analysis showed significant differences in spinal alignment between the different mattress conditions within different body shape subgroups. Subgroups were defined using body weight, height, BMI, shoulder width and hip circumference. Those with a higher body weight had a more neutral spinal alignment when on a firmer mattress, whereas those with a lower body weight were better suited to a softer mattress. Shorter people were better aligned on a softer mattress, and a medium mattress kept the spine in a more neutral position amongst taller individuals. Discussion: This study suggests that a 'one-size fits all' approach to mattresses may not be appropriate and contrasting body types need different levels of support to improve overall spinal alignment. The use of simple anthropometric measurements could make the selection of the most appropriate mattress easier for the public.